Job Analysis in Organizational Structure on Employee Performance - Alessandra Oldani; Forcella Chiara; Mozzi Monica (Yayasan Adra Karima Hubbi, 2023)
This study intends to describe job analysis in the context of human resource management (MSDI). Job analysis can be interpreted as an activity to analyze or describe the work that must be done, how to do it and why a job must be done or done. The purpose of the analysis itself varies, both general goals and specific goals specific to the company or organization itself. Job analysis also contains steps that must be followed or passed. This study concludes that job analysis is an important thing for an organization or company so that its employees are able to work more optimally and better in organizing, implementing, as well as the running of the organization or company itself which is oriented to the future. In Islam job analysis is also discussed, Islam also regulates how job analysis itself is according to the legal foundations explained in an Islamic perspective.